2010
DOI: 10.3109/08860221003675252
|View full text |Cite
|
Sign up to set email alerts
|

Cryoglobulinemic glomerulonephritis in chronic hepatitis B infection

Abstract: Hepatitis B virus (HBV) infection is an uncommon cause of cryoglobulinemia. Renal cryoglobulinemia has been rarely reported in the setting of chronic hepatitis B infection. We describe a case of chronic hepatitis B infection with cryoglobulinemic glomerulonephritis (Gn) and provide information about the treatment and the evolution over a 30-month follow-up. A 41-year-old woman with chronic hepatitis B infection developed nephrotic syndrome and acute renal failure; other investigations revealed type 2 cryoglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Therefore, the treatment of HBV‐related MC mainly includes antiviral . Whenever HBV‐related MC glomerulonephritis is associated with nephrotic syndrome and/or rapidly renal insufficiency, it has been suggested to use immunosuppressive therapy and plasma exchange . Because of the efficacy of anti‐CD20 monoclonal antibody in HCV‐related MC, it is reasonable to anticipate that anti‐CD20 antibody would be an option in HBV‐related MC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the treatment of HBV‐related MC mainly includes antiviral . Whenever HBV‐related MC glomerulonephritis is associated with nephrotic syndrome and/or rapidly renal insufficiency, it has been suggested to use immunosuppressive therapy and plasma exchange . Because of the efficacy of anti‐CD20 monoclonal antibody in HCV‐related MC, it is reasonable to anticipate that anti‐CD20 antibody would be an option in HBV‐related MC.…”
Section: Discussionmentioning
confidence: 99%
“…7 Renal involvement in patients with MC related to HBV has been poorly described, with only a few cases reported, and the optimal treatment is unclear. [8][9][10] Therefore, we must pay attention to MC patients related to HBV infection in China. The aim of this retrospective study was to investigate the clinical features and renal biopsy findings in a small group of patients with MC glomerulonephritis and evidence of hepatitis B virus infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consent forms were filled out by both patients and controls prior to blood collection. Previous studies showed that some factors such as infections [20][21][22], allergic conditions [23], and smoking [24,25] were considered as bias factors in diabetes and nephropathy; hence, patients with these bias factors were eliminated from the study using a questionnaire.…”
Section: Subjectmentioning
confidence: 99%
“…The histological deposition of circulating antigen‐antibody complexes in the mesangium and subendothelial space characterizes the MPGN associated with HBV. (Figure ) Compared with hepatitis C infection, HBV infection is a rare cause of mixed cryoglobulinaemia, which can be associated with MPGN …”
Section: Renal Disease Associated With Hepatitis Bmentioning
confidence: 99%